A COMPARATIVE STUDY ON EFFICACY AND SAFETY OF TOLPERISONE VERSUS TIZANIDINE IN PATIENTS SUFFERING FROM ACUTE LOW BACK PAIN WITH MUSCLE SPASM - KHAN, ABDUL FAHEEM; PARVEEN, KHANETA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
OBJECTIVES: The objectives of this study were to compare the efficacy and safety of Tolperisone tablets 50 mg three times daily versus Tizanidine 2 mg tablets thrice daily for the treatment of acute low back pain with muscle spasm. METHODS: The comparative study was carried out in 50 patients from orthopedics Dr. Pinnamaneni Siddhartha Institute of Medical Sciences and Research Foundation, Vijayawada. Only those patients fulfilling the inclusion/exclusion criteria were enrolled into the study. Participants suffering from acute low back pain with muscle spasm were divided into two groups. The participants were followed up on Day-14 as final analysis. RESULTS: Subjects receiving Tolperisone showed a mean value of 16.43±1.16 in the Roland Morris low back pain and disability questionnaire both groups on day 1 and was reduced to 7.82±1.15 (51.94%) on day 7 and 2.56±1.53 (84.46%) on day 14. Similarly, the patients in the tizanidine group had mean value of 15.93±1.61 on day 1, which was reduced to 6.77±1.68 (57.64%) on day 7, and 2.88±1.92 (81.95%) on day 14, as comparable to the Tolperisone group. There was no statistically significant difference between the two groups, (p>0.05) for pain at rest, pain at night, restrictions of movement, changes in stiffness, changes in numbness, and changes in tenderness. There was a statistically significant difference between the two groups, (p<0.05) for pain on movement and kinesalgia. CONCLUSIONS: Tolperisone was found comparable in efficacy to Tizanidine in improving the clinical symptoms of changes in pain Self-assessment by the patient on different applied parameters.